The Implementation of English Conversation Program in Elementary School at Rural Area - Murni Nikmatillah; Fika Megawati; Yuli Astutik (EDUCAFL : Journal of Education of English as Foreign Language, 2023)
This article discusses how to participate in Teaching campus programs and implementing English conversation programs in rural areas. Because, English is one of the subjects considered difficult by elementary school students, especially in rural areas. This research was conducted at elementary school in Tulungagung, East Java which is a rural area. This study also uses the self-study method, in which data are taken from observations and interviews with English teachers in schools to find out the difficulties or challenges in teaching and learning in rural schools, Therefore, the self-study researcher is not the self who does the research, but rather the self being studied, not that the self is the only focus. This progression in self-study characterizes teaching as well. So after that, the author compiled this conversation program. The method used in the implementation of this conversation program uses the appropriate TPR (Total Physical Response) method to support challenges or difficulties in teaching and learning. This program is carried out once every 2 weeks and is only attended by class 5. And to find out the improvement of students after joining this program, the author gives a quiz or post-test. When this activity was carried out the students were very enthusiastic and understood the questions that I gave, many improvements were obtained by them such as word pronunciation, pronunciation, word spelling, vocabulary knowledge, writing words, etc.